Peranan Pembelajaran Pendidikan Agama Islam sebagai Upaya Preventif Kenakalan Remaja di MTs Ma’arif Sikampuh Kroya Cilacap - Maulidah, Khotimatul; Yahya, M. Slamet (Matan : Journal of Islam and Muslim Society, 2023)
This research aims to discover the forms of student delinquency, the factors that cause student delinquency, and how MTs Ma'arif Sikampuh's efforts in overcoming the problem. This research is field research with primary data obtained through observation techniques and interviews with Islamic Education teachers, principals, and Counselling Guidance teachers of MTs Ma'arif Sikampuh, Kroya, Cilacap. The results showed that there are several kinds of delinquency of MTs Ma'arif Sikampuh students, which include absent without information, leaving home but not arriving at school, coloured hair and strange cut models, clothes are not inserted, fights between students, damaging school facilities, bullying through social media, storing and distributing pornographic photos or videos, saying dirty words or lacking manners towards students and teachers, hanging out outside during school hours, cheating during exams (leaving the room), bullying, and smoking in the school environment, skipping class, coming to school late, not doing homework, and making noise during the teaching and learning process. Factors that influence student delinquency are often due to lack of parental attention (broken home), the influence of friends, and from themselves because they are lazy and afraid of teachers. The school's efforts to overcome student delinquency are preventive through religious activities or providing religious education, guiding extra-curricular activities, and increasing the effectiveness of parental and community relations (public relations).